Recherches sur les technologies de l’information et de la communication et le développement - Alain Kiyindou (Communiquer)
The relationship between technology and development involves two major terms of our discipline. First, the technology, that has become a focus in communication, and development, which is an objective shared by individuals, institutions, societies, and nations. But beyond the technology is the digital in question. This relationship, if it is increasingly questioned, provoked reflections far back and are linked to traditional or conventional technologies. For the communication researcher, several questions arise : they concern the optimal conditions for its use, the factors promoting its adoption and the causes of resistance. What makes a technology or a technological application knows an unexpected success, while others struggle to get adopted ? How does technology change practices in development ?